The yin and yang of autophagy in acute kidney injury - Melk, Anette (Autophagy, 2016)
Antagonizing the strongly activated pathway of autophagy in renal ischemic injury has been associated with poor outcome. In our recent study we used mice with a selective deletion of Atg5 in the S3 proximal tubule segment, which is most susceptible to ischemic damage. In line with the notion that autophagy is a prosurvival mechanism our studies revealed an early accelerated cell death of heavily damaged tubular cells in the S3 segment of these mice. Interestingly, this expedited loss of cells was associated with better long-term outcome as reflected by less inflammation, improved tubular repair, and function and reduced accumulation of senescent cells. While these data confirm the role of tubular autophagy as a prosurvival mechanism in ischemic kidney injury, they also show that autophagy may enable severely damaged cells to persist and exert deleterious effects. Such ambivalent effects might be of relevance if modulating autophagy is considered as a therapeutic option.